Exploring Higher Education Learners’ Experience of Utilizing Gemini Chatbot in English Language Learning - Nancy Putri Utami; Kembaren, Farida Repelitawaty; Daulay, Sholihatul Hamidah (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The tremendous progress in Artificial Intelligence (AI) and Natural Language Processing (NLP) has resulted in the creation of advanced chatbots that can participate in intricate conversations. This research investigates university students' experiences using the Gemini chatbot for learning English as a second language. It emphasizes the advantages as well as the difficulties encountered. A case study method was used to observe and interview 10 students from a public institution in North Sumatra. The findings indicate that the Gemini chatbot's interface, which is easy to use, the comprehensive feedback it provides, and its wide range of capabilities have a substantial positive impact on students' language proficiency and self-assurance. Nevertheless, several constraints were observed, including imprecise translations, problems with speech recognition, and technological challenges such as poor internet connections. Effective approaches to address these obstacles including using alternate educational materials, implementing well-organized study timetables, participating in virtual learning groups, and employing formal language to enhance communication clarity with the chatbot. This study offers useful insights for educational institutions and policymakers on the optimization of AI chatbots in language teaching university students' experiences using the Gemini chatbot for learning English as a second language. to successfully enhance student learning.